T-regulatory cells require Sin3a for stable expression of Foxp3 - Christensen, Lanette M.; Akimova, Tatiana; Wang, Liqing; Han, Rongxiang; Samanta, Arabinda; Di Giorgio, Eros; Hancock, Wayne W. (Frontiers in Immunology, 2024)
Histone deacetylases 1 and 2 play a major role in transcriptional regulation of T-regulatory cells via interactions with a myriad of co-regulatory factors. Sin3a has been well established as a Hdac1/2 cofactor, while its role within Tregs has not been established. In this study the effects of conditional deletion of Sin3a within Foxp3+ Tregs were evaluated. Developmental deletion of Sin3a from Foxp3+ Tregs resulted in the rapid onset of fatal autoimmunity. Treg numbers were greatly reduced while residual Tregs had impaired suppressive function. Mice also showed effector T cell activation, autoantibody production, and widespread tissue injury. Mechanistically, Sin3a deletion resulted in decreased transcription of Foxp3 with complete lack of CNS2 CpG demethylation. In addition, Foxp3 protein stability was impaired with an increased ex-Treg population. Thus, Sin3a plays a critical role in the maintenance of Treg identity and function and is essential for the expression and stability of Foxp3. Mice and cell lines. We purchased Ai9(RCL-tdT) (stock #007909) and TAM-inducible Foxp3cre (stock #016961) mice from The Jackson Laboratory, in addition to previously described Foxp3 YFP-cre (46), CD4 cre (47) and Sin3a flox/flox (48) mice. Sin3a -/-Foxp3 YFPcre mice and Foxp3 YFPcre controls were used 12-15 days after birth due to the early onset of lethal autoimmunity in mice with conditional deletion of Sin3a in their Tregs, whereas inducible KO mice were used at 6-8 weeks. Mice were housed and handled in accordance with IACUC (protocol #IAC-22-000561) and The Children's Hospital of Philadelphia Research Institute policy. The 293T cell line used in this study was obtained from the ATCC repository (CRL-3216).Histology. Sections of formalin-fixed, paraffin-embedded tissues were stained with hematoxylin and eosin (H&E) and analyzed in a blinded manner by a pathologist.Detection of autoantibodies. Cryosections (4-5 µM) of unfixed normal tissues were incubated for 1 hr at RT with Sin3a -/-Foxp3 YFPcre sera, washed, incubated for 30 min at RT with FITC-labeled goat antimouse secondary Ab, washed and mounted. Pre-characterized sera from mice with known autoantibodies were used as positive controls, while pooled normal sera and secondary Abs alone were used as negative controls.